TINJAUAN YURIDIS TENTANG PERLINDUNGAN HUKUM TERHADAP PEKERJA OUTSOURCING - Rahmatullah Rahmatullah; Rizka Amelia Armin (MADDIKA : Journal of Islamic Family Law, 2021)
Outsourcing in Indonesian labor law is defined as the contracting of work and the provision of labor services. The legal arrangements for outsourcing in Indonesia are regulated in the Manpower Act Number 13 of 2003 (articles 64, 65 and 66) and the Decree of the Minister of Manpower and Transmigration of the Republic of Indonesia No. Kep.101/Men/VI/2004 of 2004 concerning Procedures for Licensing for Workers/Labour Service Providers (Kepmen 101/2004). In general, the rights of outsourced employees are getting wages, getting overtime pay, getting leave rights, getting THR (Tunjangan Hari Raya), getting Jamsostek protection, getting layoff compensation.